Enhanced gas sensing properties of hierarchical SnO2 nanoflower assembled from nanorods via a one-pot template-free hydrothermal method. Issue 14 (1st November 2016) - Wang, Qiong; Yao, Na; An, Dongmin; Li, Yan; Zou, Yunling; Lian, Xiaoxue; Tong, Xiaoqiang
Abstract: Well-defined three-dimensional (3D) hierarchical tin dioxide (SnO2 ) nanoflowers with the size of about 200 nm were successfully synthesized by a simple template-free hydrothermal method. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and N2 adsorption-desorption analyses were used to characterize the structure and morphology of the products. The as-synthesized full crystalline and large specific surface area SnO2 nanoflowers were assembled by one-dimensional (1D) SnO2 nanorods with sharp tips. A possible self-assembly mechanism for the formation the SnO2 nanoflowers was speculated. Moreover, gas sensing investigation showed the sensor based on SnO2 nanoflowers to exhibit high response and fast response-recovery ability to detect acetone and ethanol at an operating temperature lower than 200 °C. The enhancement of gas sensing properties was attributed to their 3D hierarchical nanostructure, large specific surface area, and small size of the secondary SnO2 nanorods. Graphical abstract: